2007
DOI: 10.1159/000175156
|View full text |Cite
|
Sign up to set email alerts
|

The Plasminogen Activator System and Cancer

Abstract: The fibrinolytic system, more appropriately referred to as the plasminogen activator system, controls not only the intravascular fibrin deposition but also participates in a wide variety of physiologic and pathologic processes. In cancer, the components of this system are involved in tumor growth, invasion and metastasis, through their effect on angiogenesis and cell migration. These components are found in most tumors and their expression signifies not only their function but also carries a prognostic value. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
106
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 147 publications
1
106
1
3
Order By: Relevance
“…It has been shown that matrix metalloproteinase1 (MMP1), which is involved in the breakdown of extracellular matrix proteins, plays a role in tissue remodeling and metastasis [58][59][60] through collagen destruction, which causes progression in cardiac dysfunction [61]. The role of plasminogen activator urokinase (PLAU) and plasminogen activator tissue (PLAT) in extracellular matrix degradation and possible tumor cell migration and proliferation has also been highlighted [62][63][64][65]. ell cycle-related genes were downregulated through subsequent passages.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that matrix metalloproteinase1 (MMP1), which is involved in the breakdown of extracellular matrix proteins, plays a role in tissue remodeling and metastasis [58][59][60] through collagen destruction, which causes progression in cardiac dysfunction [61]. The role of plasminogen activator urokinase (PLAU) and plasminogen activator tissue (PLAT) in extracellular matrix degradation and possible tumor cell migration and proliferation has also been highlighted [62][63][64][65]. ell cycle-related genes were downregulated through subsequent passages.…”
Section: Discussionmentioning
confidence: 99%
“…11 Plasmin degrades components of the ECM both directly and indirectly through activation of MMPs and cytokines involved in both tissue repair and malignant growth. 12,13 Several studies have shown that increased levels of uPAR is linked to poor prognosis in a number of cancers, including pulmonary carcinomas, colorectal and breast cancer. 8,[14][15][16] We recently reported that uPAR in gastric cancers is frequently expressed in cancer cell populations, 17 which are likely directly linked to the malignancy of the disseminated cancer cells in the bone marrow.…”
mentioning
confidence: 99%
“…По известным нам данным, биологическая роль различных изоформ VEGFA остается не до конца определенной [8,9,17]. Так, VEGAF121 и VEGFA165 секретируются в эндотелиальных клетках и спо-собствуют их активному митогенезу [10,11,18]. Изоформы с большим количеством аминоки-слот -VEGFA165 и VEGFA189 -ассоциируются в основном с присутствием в клетках, хотя тоже обладают сосудистой проницаемостью [10,17].…”
Section: Discussionunclassified
“…Изоформы с большим количеством аминоки-слот -VEGFA165 и VEGFA189 -ассоциируются в основном с присутствием в клетках, хотя тоже обладают сосудистой проницаемостью [10,17]. Считается, что VEGFA165 более «выгодна» для опу-холи, чем VEGFA189, хотя обе изоформы участвуют в локальном ангиогенезе [11,17,18]. Отмечено, что при дефиците VEGFA165 компенсаторно повы-шается уровень VEGFA189, однако это не сопро-вождается усилением инвазии опухоли в костный мозг [17,18].…”
Section: Discussionunclassified
See 1 more Smart Citation